Promama Complementary Therapy: Impact on Hemoglobin, Weight, Anxiety, Nausea and Vomiting of Pregnancy (NVP) - Nur Maziyah Hurin'in; Tri Yunita Fitria Damayanti; Nur Cholila; Gita Aprilia Ayu Masfufah; Tuadhatun Nuriyawati (Biomedical Journal of Indonesia, 2026)
Introduction. Nausea and vomiting are among the most common discomforts experienced by pregnant women in the first trimester, often leading to decreased nutritional intake, weight loss, and anemia, which may ultimately affect maternal and fetal health. Various complementary interventions, including acupressure, moxibustion, and ginger aromatherapy, have been developed as supportive therapies to reduce these symptoms. This aimed to analyze the effectiveness of PROMAMA is a combined intervention of acupressure, moxibustion, and ginger aromatherapy for nausea and vomiting of pregnancy in reducing nausea, vomiting, anxiety, and anemia, as well as improving weight gain. Methods. This quasi-experimental study employed a pre-test-post-test control group design with 120 first-trimester pregnant women who met the inclusion criteria. Participants were divided into three groups: control, Standard, and intensive intervention. Data were collected using the PUQE-24 (Pregnancy-Unique Quantification of Emesis and Nausea), GAD-7 (Generalized Anxiety Disorder-7), hemoglobin measurements, and maternal weight records. Statistical analyses included One-Way ANOVA, ANCOVA, and Independent Sample T-Test. Results. The findings revealed significant differences between the groups in reducing nausea and vomiting, anxiety, and hemoglobin levels at post-test 1 and post-test 2 (p < 0.05). Intensive interventions combining acupressure, moxibustion, and ginger aromatherapy showed greater effectiveness compared to Standard and control groups. However, no significant differences were observed in weight gain across the groups (p > 0.05). Conclusion. Acupressure, moxibustion, and ginger aromatherapy are effective for managing nausea, vomiting, anxiety, and anemia in first-trimester pregnant women. These interventions can be recommended as non-pharmacological approaches to improve maternal well-being and pregnancy outcomes.